2022
DOI: 10.3390/ijms232415627
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adiponectin in Cardiovascular Diseases Related to Glucose and Lipid Metabolism Disorders

Abstract: Lifestyle changes have led to increased incidence of cardiovascular disease (CVD); therefore, potential targets against CVD should be explored to mitigate its risks. Adiponectin (APN), an adipokine secreted by adipose tissue, has numerous beneficial effects against CVD related to glucose and lipid metabolism disorders, including regulation of glucose and lipid metabolism, increasing insulin sensitivity, reduction of oxidative stress and inflammation, protection of myocardial cells, and improvement in endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…This study found that CSPHs‐Ca and XOS‐CSPHs‐Ca‐TG decreased adiponectin concentrations, resistin, and visfatin in adipocytes ( p < .05). Adiponectin, an adipokine exclusively secreted by adipocytes, could stimulate fatty acid oxidation, reduce plasma labeling, and improve glucose metabolism (Han et al., 2022). After culture with CSPHs‐Ca and XOS‐CSPHs‐Ca‐TG, adiponectin in adipocytes was significantly decreased compared with the control group ( p < .05) (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…This study found that CSPHs‐Ca and XOS‐CSPHs‐Ca‐TG decreased adiponectin concentrations, resistin, and visfatin in adipocytes ( p < .05). Adiponectin, an adipokine exclusively secreted by adipocytes, could stimulate fatty acid oxidation, reduce plasma labeling, and improve glucose metabolism (Han et al., 2022). After culture with CSPHs‐Ca and XOS‐CSPHs‐Ca‐TG, adiponectin in adipocytes was significantly decreased compared with the control group ( p < .05) (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…However, adiponectin and IL-6 are both substantially expressed in AT [ 49 , 62 , 63 ] and closely related to their respective serum concentrations [ 48 ]. Both molecules represent inflammatory markers in people with obesity and T2D [ 62 , 63 , 64 ] and may affect glucose and lipid metabolism [ 65 , 66 , 67 , 68 ]. Average adipocyte size and adipocyte hypertrophy are important determinants of altered CA5A and adiponectin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin has anti-apoptotic, anti-inflammatory, anti-swelling, and antioxidant effects [100]. Adiponectin has a cardioprotective effect by affecting autophagy with hypertrophy, inhibiting atherogenesis and apoptosis, reducing lipotoxic damage and ROS production, and promoting cell viability [100][101][102]. Anti-inflammatory effects of adiponectin include its action on macrophages and endothelial cells [101].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Anti-inflammatory effects of adiponectin include its action on macrophages and endothelial cells [101]. It also has a blood-pressurelowering effect [101]. Adiponectin is referred to as a "rescue hormone" because of its role in preventing heart injury [100].…”
Section: Cardiovascular Systemmentioning
confidence: 99%